2005
DOI: 10.1371/journal.pbio.0030324
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Wide-Spectrum Inhibitors Targeting Coronavirus Main Proteases

Abstract: The genus Coronavirus contains about 25 species of coronaviruses (CoVs), which are important pathogens causing highly prevalent diseases and often severe or fatal in humans and animals. No licensed specific drugs are available to prevent their infection. Different host receptors for cellular entry, poorly conserved structural proteins (antigens), and the high mutation and recombination rates of CoVs pose a significant problem in the development of wide-spectrum anti-CoV drugs and vaccines. CoV main proteases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
815
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 650 publications
(839 citation statements)
references
References 47 publications
19
815
3
2
Order By: Relevance
“…pro (Yang et al, 2005). To be consistent with that the high similarities between the key residues of CoV 3CL pro s for substrate recognition, we found that N3 can effectively inhibit the proteolytic activity of HCoV-EMC 3CL pro with an IC 50 of 0.28 ± 0.02 μmol/L (Fig.…”
Section: Referencessupporting
confidence: 82%
See 1 more Smart Citation
“…pro (Yang et al, 2005). To be consistent with that the high similarities between the key residues of CoV 3CL pro s for substrate recognition, we found that N3 can effectively inhibit the proteolytic activity of HCoV-EMC 3CL pro with an IC 50 of 0.28 ± 0.02 μmol/L (Fig.…”
Section: Referencessupporting
confidence: 82%
“…Since 3CL pro is unique in the virus but not found in the host cell, this protein is a prominent target for the development antivirals against CoV infections (Yang et al, 2005), and a number of inhibitors have been discovered that prohibit the infection of CoV through their action on 3CL pro (Yang et al, 2005).…”
mentioning
confidence: 99%
“…Here, we also present the cocrystal structure of IBV M pro in complex with N3, a wide-spectrum inhibitor that we designed previously to target CoV M pro s (34). We further demonstrate its rapid in vitro inactivation against the viral protease and potent antiviral activity toward IBV in chicken embryos.…”
mentioning
confidence: 87%
“…It was reported to be 10 or 100 times more potent inhibitor of SARS-CoV than IFN-∝ and IFN-β, respectively (He et al, 2004) Chloroquine A clinically approved drug for malaria was effective with an IC50 in lower µM range (Keyaerts et al, 2004). In addition to its effect through elevation of endosomal pH, chloroquine seems to interfere with terminal glycosylation of ACE2, the the receptor for SARS-CoV (Vincent et al, 2005 (Li et al, 2005a;Wu and Huang, 2005;Zhao and Qin, 2005;Tang and Li, 2008) Homology modeling also formed a basis for designing mechanism-based irreversible inhibitors of 3CLpro with an activity of wide spectrum across coronaviruses (Yang et al, 2005a). Besides, several groups have identified a number of inhibitors of 3CLpro using a variety of approaches.…”
Section: Viral Protease Inhibitorsmentioning
confidence: 99%